The theories of combinatory as a syntactical characteristic of predicates (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The paper focuses on the language units valency in the structure of syntactical patterns, as well as on the regularities of functioning of mechanisms that define sentence formation principles. A special emphasis is placed on the role of predicate, the combinative properties of which determine the syntactical units construction .
Keywords: valency; distribution; intention; syntactical combinability; predicate; argument